Big Jake [videorecording (Blu-Ray)] - Cabot, Bruce, 1904-1972; Wayne, John, 1907-1979; Wayne, Patrick, 1939-; Boone, Richard; O'Hara, Maureen, 1920-2015; Fink, Harry Julian; Fink, R. M. (Rita M.); Wayne, Michael, 1934-2003; Sherman, George, 1908-1991 (Paramount Home Entertainment, 2011)
Big Jake McCandles hasn't seen his wife in over nine years, but he returns home after his grandson is kidnapped by a vicious outlaw gang. While the law gives chase in rickety automobiles, Jake saddles up with an Indian scout and a box of money, even though paying a ransom isn't how Jake plans to exact good old frontier justice.